2017
DOI: 10.1016/j.ijporl.2017.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Australian children with cleft palate achieve age-appropriate speech by 5 years of age

Abstract: Children with cleft palate are prone to phonetic and phonological speech errors in their preschool years. Most of these speech errors approximate typically-developing children by 5 years. At 3 years, word shape has an influence upon phonological speech accuracy. Speech pathology intervention is indicated to support the intelligibility of these children from their earliest stages of development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Differential diagnosis of presenting speech symptoms-structural versus mislearned errors-can be challenging and is often facilitated by diagnostic speech therapy to inform treatment decision-making (Marsh, 2004). Further to articulation difficulties, increased phonological errors are reported in cleft palate populations, but not routinely considered amongst individuals with SMCP (Chacon, Parkin, Broome, & Purcell, 2017;Chapman, 1993;Schönweiler et al, 1999). Phonological error patterns occur at a cognitive-linguistic level and manifest in errors of speech sound processing rather than consonant production (Dodd, Leahy, & Hambly, 1989;Grunwell, 1975).…”
mentioning
confidence: 99%
“…Differential diagnosis of presenting speech symptoms-structural versus mislearned errors-can be challenging and is often facilitated by diagnostic speech therapy to inform treatment decision-making (Marsh, 2004). Further to articulation difficulties, increased phonological errors are reported in cleft palate populations, but not routinely considered amongst individuals with SMCP (Chacon, Parkin, Broome, & Purcell, 2017;Chapman, 1993;Schönweiler et al, 1999). Phonological error patterns occur at a cognitive-linguistic level and manifest in errors of speech sound processing rather than consonant production (Dodd, Leahy, & Hambly, 1989;Grunwell, 1975).…”
mentioning
confidence: 99%
“…The importance of a developmental approach is evidenced by studies in this review, as both Chacon et al . () and Hutters et al . (2011) reported that children with CP±L present with more developmental phonological processes at 3 years of age than their non‐cleft peers.…”
Section: Discussionmentioning
confidence: 88%
“…This was supplemented in the studies of Chacon et al . (), Chapman et al . (), Chapman () and Morris and Ozanne () by computer software to aid the analysis of articulation and phonology.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations